PERBANDINGAN INTERVENSI AUTO STRETCHING DAN ACTIVE ISOLATED STRETCHING TERHADAP PENURUNAN NYERI OTOT UPPER TRAPEZIUS PADA PEGAWAI NEGERI SIPIL DI DINAS KELAUTAN DAN PERIKANAN PEMERINTAH PROVINSI BALI - I Gusti Bagus Ari Pradnyana Putra; Ari Wibawa; Susy Purnawati; Ni Wayan Tianing (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACT The research is aimed to know abour the difference between Auto Stretching exercise and Active Isolated Stretching on reduction of Upper Trapezius muscle pain on civil Servants of Ministry of Maritime and Fisheries in Bali Province. The giving of intervention of Active Isolated Stretching was better in reducing Upper Trapezius muscle pain than Auto Stretching intervention of office employees. This research was experimental randomized pre-post test two group design which involved 24 people as samples which was divided into 2 groups, the firs group with Auto Stretching and the second with Active Isolated Stretching. After getting the results, the normality test was done using Levene’s test for further, statistic test was done using Independent Sample T-test. The results of the test shown that the mean of the first group (1,16±0,167) and the second group (1,66±0,220) and would mean (p < 0,05). The conclusion of this research is Active Isolated Stretching reduced more Upper Trapezius muscle pain intensity than Auto Stretching on Civil Servants of Ministry of Maritime and Fisheries in Bali Province. Keywords: Auto Stretching, Active Isolated stretching, Upper Trapezius Muscle, VAS.